Synthesis of New 3-Substituted Quinazolin-4(3H)-one Compounds Via Linking of Some Five-Membered Ring Heterocyclic Moieties With Quinazolin-4(3H)-one Nucleus - Mohammed Al-iraqi; Rand Saad-Aldeen (College of Education for Pure Sciences, 2021)
In this research new compounds containing quinazolin-4(3H)-one nucleus linked to heterocyclic moieties were synthesized using ethyl (4'-oxoquinazolin-3'-yl) acetate (2) as a synthon. This compound was synthesized via 4-quinazolinone's (1) reaction with ethyl chloroacetate in the existence of K2CO3 as a base and acetone as a solvent. The ethyl α-(4'-oxoquinazolin-3'-yl) acetate (2) was converted to the corresponding hydrazide through its reaction with hydrazine hydrate (85 %). Compound (3) was reacted with two of acyl chlorides to synthesize the diacyl hydrazine compounds (4,5). The compound (5) was cyclized to the corresponding 1,3,4-oxadiazole (6) in presence of phosphorous oxychloride. The formyl derivative (7) of the hydrazide (3) was synthesized via its reaction with formic acid and consequently cyclized by phosphorous oxychloride to the corresponding 1,3,4-oxadiazole (8). The hydrazide (3) was also converted to the thiosemicarbazide derivative (9) by its reaction with ammonium thiocyanate under acidic conditions. Whereas other substituted thiosemicarbazide derivatives (10-12) were synthesized by the reaction of hydrazide (3) with organic isothiocyanate compounds. The resultant compounds (11, 12) were cyclized under basic conditions (4% sodium hydroxide solution) to give 1,3,4-triazole-2-thiole derivatives (13,14), whereas the cyclization of compounds (10-12) was performed under the acidic medium (conc. H2SO4) to give 2-substituted amino-1,3,4-thiadiazoles (15-17). On the other side, the hydrazide's (3) reaction with isocyanate compounds affords the semicarbazide compounds (18,19). These compounds were cyclized under the basic condition to afford 1,3,4-triazol-2-ol compounds (20,21). The structures of the synthesized compounds were corroborated depending on the physical and spectral data.